Diversity of butterfly (Lepidoptera: Papilionoidea) and its potential role as entomotourism product in Gunung Ledang, Malaysia - Atirah Aisyah Hasnizan,; Norradihah Ismail,; Maryati Mohamed,; Halid Mohd Salleh, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2021)
Entomotourism is part of nature-based tourism that uses insect as a product. In this study, butterfly was chosen to be proffered as new attraction in Gunung Ledang, Malaysia. The objectives are to i) determine the diversity of butterfly, ii) select ten most charismatic species based on the eight criteria currently used for development of nature tourism product and iii) produce a souvenir prototype. The samplings were done manually using aerial net and baited trapping along 1 km transect in Gunung Ledang Resort trail over six sampling occasions between January to July 2019. This study recorded 40 species comprising of 89 individuals from six families, thus successfully added twelve new records for Gunung Ledang. Butterfly fauna in sampling area considered diverse supported by Shannon diversity index of 3.388 and had even species distribution as species evenness index of 0.906. From the total number of species, ten short-listed of butterfly species had met six criteria of a good nature tourism product: safety, rarity, attractive morphology, behavioural enticement, reliability of sightings, and ecologically important. The species are Graphium sarpedon luctatius, G. agamemnon agamemnon, Papilio polytes romulus, P. memnon agenor, P. nephelus sunatus, Eurema hecabe contubernalis, Idea hypermnestra linteata, Zeuxidia doubledayi doubledayi, Euploea radamanthus radamanthus, and Elymnias casiphone saueri. Brochure and souvenir prototypes were developed based on the selected species that portrayed local image which could potentially be added to the existing attractions. Overall, much of the research is about to diversify tourism products which is in line with the Malaysia Government’s agenda and also, point out the need to conserve Gunung Ledang.